The U.S. Constitution and the separation of powers - Duignan, Brian; DeCarlo, Carolyn (Checks and balances in the U.S. government., 2019)
Explores the history of the U.S. Constitution, what it says and enforces about the separation of powers between the branches of government, and how the separation of powers has played out in important events and court cases in U.S. history.